World Journal of Surgical Oncology reviewer acknowledgement 2012 - Pandey, Manoj (BioMed Central, 2013)
CONTRIBUTING REVIEWERS: The editor of World Journal of Surgical Oncology would like to thank all our reviewers who have contributed to the journal in Volume 10 (2012).